Model Kerjasama Antar Perpustakaan Umum Dalam Negeri - Ika Wardani; Miftahyl Fikri; Muhammad Farhan Maulana; Yusniah Yusniah (Da'watuna: Journal of Communication and Islamic Broadcasting, 2023)
In order to produce energy in the pursuit of achievement, public libraries that are open to all citizens must collaborate and network. It enables broad access to collection, better user and technical services, increased resource sharing activities, decreased duplication, and the creation of an effective service. In order to achieve the establishment of collaboration and networking in the setting of public libraries, a foundation should take a number of factors into account. Keywords: Public Library, Library Cooperation, Library Networking